A brief, theory-driven patient education video reduces high-risk over-the-counter nonsteroidal anti-inflammatory drug (NSAID) use - Matthew G. Vinson; Allison N. Tegge; Mamata R. Tokala; Cara R. Spivey; Martha M. Tenzer; Jeffrey S. Stein; John W. Epling; Michelle S. Rockwell (PLoS ONE, 2025)
Professional guidelines advise against regular or long-term NSAID use in most patients with chronic kidney disease (CKD), heart failure (HF), and hypertension (HTN) due to risk of adverse events. Nevertheless, over-the-counter (OTC) NSAIDs are broadly accessible and frequently used among this population. Efforts to decrease high-risk OTC NSAID use have the potential to improve safety and reduce chronic disease burden. This randomized controlled trial evaluated the effectiveness of a brief, electronically-administered educational video in reducing high-risk OTC NSAID use. Adult participants with CKD, HF, and/or HTN who self-identified as regular NSAID users (≥3 times/week for 3 months) were invited to participate. Participants (n = 425) were randomized to either view an electronically-administered educational video informed by the COM-B behavioral change model (VIDEO, n = 223) or the FDA Drug Facts label for NSAIDs (CONTROL, n = 202). Intent to decrease OTC NSAIDs was evaluated via 11-point contemplation ladder immediately and 4 weeks post-intervention, with self-reported NSAID Exposure assessed at 4 weeks. We also evaluated current and recent pain levels at baseline and 4 weeks. Intent to decrease OTC NSAID use (4.28 (SD: 3.45) ladder rungs) and NSAID exposure (20.14 (SD: 13.66) dose-days per month) did not differ between groups at baseline. Intent to decrease OTC NSAID use increased more from baseline to immediately post-intervention in VIDEO vs. CONTROL (1.32 (SD: 2.80) vs. 0.55 (SD: 1.99) rungs, p < 0.001), with greater improvements for those with lower baseline intent. VIDEO and CONTROL were associated with a similar rise in intent to decrease OTC NSAID use (1.92 (SD: 4.41) vs. 1.36 (SD: 3.46), p = 0.150) and a similar decrease in NSAIDs exposure (−32.8% in VIDEO and −36.5% in CONTROL, p = 0.520) 4 weeks post-intervention. Pain levels did not differ between groups. Results suggest that a low-burden, electronically-administered intervention reduce high-risk medication use among patients with CKD, HF, and/or HTN.